(untitled) (Patrimônio e Memória, 2018)
In 1979, urban preservation policies were developed in Rio de Janeiro, mostly in response to the wave of urban renewal and the demolition of iconic, early-20th century buildings in the city’s downtown area. The City of Rio de Janeiro began to draw the attention of intellectuals and civil servants who wished to protect a specific urban ensemble, consisting of buildings valued for their commonplace character, i.e., a particular type of nonmonumental architecture. These urban planning decisions culminated with the passing of the 1983 “Cultural Corridor” preservation law, which was much talked about across Brazil. Despite its success, the project remains an almost unique example of the intersection of urban planning and cultural heritage within the country. Given the limited critical discussion on this matter, this paper aims to examine the history of preservation and non-preservation actions in Rio de Janeiro, and the way in which cultural heritage became the focus of urban policies years after the systematic transformation of its downtown area.